# Find nth term of Geometric Sequence a = 3, n = 6, and r =3

**Created By :** Abhinandan Kumar

**Reviewed By :** Phani Ponnapalli

**Last Updated :** Mar 21, 2023

Find nth term of Geometric Sequence a = 3, n = 6, and r =3 easily by taking help of our easy yet handy Geometric Sequence Calculator and get the result 729 easily.

## The nth term of Geometric Sequence a = 3, n = 6, and r =3 is 729

Steps to find nth term of geometric sequence:

**nth term of geometric sequence formula:-**

a_{n} = a * r^{(n-1)}

**where:**

- a
_{n}is the nth term - a is first term
- n is total number of terms
- r is common ratio

**Input values are:-**

a = 3

n = 6

r = 3

**Put values into formula**

a_{n} = a * r^{(n-1) }

a_{6} = 3*3^{ (6-1) }

**a _{6} = 729**

Below is the step by step procedure to determine the nth term of Geometric Progression(G.P) a = 3, n = 6, and r =3. Follow this detailed process and arrive at the solution easily.

- Firstly, identify the given terms of the sequence i.e. a = 3, n = 6, and r =3
- Now, substitute the know values in the formula of finding nth term of Geometric Sequence i.e. a
_{n}= a*r^{(n-1)}= a_{5}= 3*3(6-1) - Simplifying further we get the resultant value a
_{5}= 729

### Example for Finding nth term of Geometric Sequence

### FAQs on Finding nth Term of Geometric Sequence a = 3, n = 6, and r =3

**1. What is the formula for nth term of Geometric Progression?**

The formula for nth term of Geometric Progression is given by the equation a_{n} = a*r^{(n-1)}

**2. How do you find the nth term of Geometric Sequence a = 3, n = 6, and r =3?**

You can find the nth term of Geometric Sequence a = 3, n = 6, and r =3 by substituting in the formula of nth term of G.P i.e. an = a*r^{(n-1)} = a_{5} = 3*3^{(6-1)}

**3. Where do I find the Detailed Steps for finding the nth term of Geometric Sequence a = 3, n = 6, and r =3?**

You can find the detailed steps for finding the nth term of Geometric Sequence a = 3, n = 6, and r =3 on our page.